A Review On Ankylosing Spondylitis - V. SANTHOSH KUMAR,; SUKIRTI DAS,; T.SAI SAMPATH, (International Journal of Pharma and Bio Sciences, 2011)
Ankylosing spondylitis is a chronic autoinflammmatory disease of the joints, belonging to the group of spondyloarthropathic disorders. The disease has a crippling effect on the axial skeleton and its progression to the later stages can have a debilitating effect on the patient. It has an under-diagnosed pathology and enigmatic pathophysiology. A strong genetic link has been found with the help of genome screening. Evidence of proinflammatory cytokines has been suggested but the unique aspect is that inflammation and structural progression are partly independent. DMARDS, NSAIDS produce symptomatic relief and anti-TNF therapy shows promising results. Current research has to delve deep into the pathophysiology for development of an ideal, curative therapy.